2010
DOI: 10.1074/jbc.m109.088872
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial MazG Is a Novel NTP Pyrophosphohydrolase Involved in Oxidative Stress Response

Abstract: MazG nucleoside triphosphate pyrophosphohydrolase (NTP-PPaseMycobacterium tuberculosis H37Ra is an avirulent relative of the typical laboratory strain H37Rv, both of which are derived from the parent strain H37 that was originally isolated from a 19-year-old patient with chronic pulmonary tuberculosis by Edward R. Baldwin in 1905 (1). Our systematic comparison of the complete genomic sequences of H37Rv and H37Ra identified multiple H37Ra-specific single nucleotide polymorphisms (SNPs) affecting about 30 genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 38 publications
(63 reference statements)
1
54
0
Order By: Relevance
“…The species of the MTBC that DS6A is known to infect (M. tuberculosis, M. bovis, M. canettii, M. microti, and M. africanum) grow slowly, with doubling times of at least 16 h. The presence of MazG, a nucleoside triphosphate pyrophosphohydrolase known to upregulate the host metabolism (42), was also thought to be required by DS6A for efficient propagation and to serve the need to propagate faster than the division time of M. tuberculosis. Surprisingly, the presence and absence of mazG in ⌽ 2 GFP12 and ⌽ 2 GFP13, respectively, did not affect fitness, and both phages generated titers comparable to that of wild-type DS6A.…”
Section: Discussionmentioning
confidence: 99%
“…The species of the MTBC that DS6A is known to infect (M. tuberculosis, M. bovis, M. canettii, M. microti, and M. africanum) grow slowly, with doubling times of at least 16 h. The presence of MazG, a nucleoside triphosphate pyrophosphohydrolase known to upregulate the host metabolism (42), was also thought to be required by DS6A for efficient propagation and to serve the need to propagate faster than the division time of M. tuberculosis. Surprisingly, the presence and absence of mazG in ⌽ 2 GFP12 and ⌽ 2 GFP13, respectively, did not affect fitness, and both phages generated titers comparable to that of wild-type DS6A.…”
Section: Discussionmentioning
confidence: 99%
“…Many marine phages have proteins containing MazG domains, suggesting the importance of this domain in the proliferation of marine phages (44)(45)(46). In bacteria, MazG domain proteins have been shown to function in stress responses or removal of noncanonical nucleotides (47)(48)(49). It has been suggested that phage MazG proteins may contribute to phage propagation by helping sustain the metabolism of starved host bacteria (44,46).…”
Section: Resultsmentioning
confidence: 99%
“…5 deduced amino acid sequences shared 46-52 % amino acid sequence identity with the virion proteins of PaMx42. (Gross et al, 2006;Lu et al, 2010). Under stress conditions, unusual nucleotides begin to accumulate in the cell, facilitating the programmed cell death.…”
mentioning
confidence: 99%